2015
DOI: 10.1016/j.micres.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin from psychrotrophic Sphingomonas faeni exhibits antagonism against food-spoilage bacteria at low temperatures

Abstract: Food production and processing industry holds a perpetual relationship with microorganisms and their by-products. In the present study, we aimed to identify beneficial cold-adapted bacteria devoid of any food spoilage properties and study their antagonism against common food-borne pathogens at low temperature conditions. Ten isolates were obtained on selective isolation at 5 °C, which were spread across genera Pseudomonas, Sphingomonas, Psychrobacter, Leuconostoc, Rhodococcus, and Arthrobacter. Methanol extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Numerous studies have demonstrated the effectiveness of AMF on alleviating drought and salinity stresses (Evelin et al 2009;Fan and Liu 2011;Abdel-Fattah and Asrar 2012;Zhang, Zhang, and Huang 2014;Bernardo et al 2017;Quiroga et al 2017;Selvakumar et al 2017). However, not so much information is available regarding the influence of AMF on conferring tolerance to low temperatures (Charest et al 1993;Zhu et al 2010a,b;Zhu et al 2016; Abdel Latef and Chaoxing 2011; Chen et al 2013Chen et al , 2014Liu et al 2014) and bacteria (Theocharis et al 2011;Fernandez et al 2012;Su et al 2015;Subramanian et al 2015Subramanian et al , 2016Srinivasan et al 2017). More importantly, because of the adverse effects of low temperatures on symbiosis, improving plant and microbiome performance and tolerance to cold stress, which depends on plant-symbiont, symbiont-symbiont interactions, and symbiont activity threshold under cold climatic conditions, requires more investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the effectiveness of AMF on alleviating drought and salinity stresses (Evelin et al 2009;Fan and Liu 2011;Abdel-Fattah and Asrar 2012;Zhang, Zhang, and Huang 2014;Bernardo et al 2017;Quiroga et al 2017;Selvakumar et al 2017). However, not so much information is available regarding the influence of AMF on conferring tolerance to low temperatures (Charest et al 1993;Zhu et al 2010a,b;Zhu et al 2016; Abdel Latef and Chaoxing 2011; Chen et al 2013Chen et al , 2014Liu et al 2014) and bacteria (Theocharis et al 2011;Fernandez et al 2012;Su et al 2015;Subramanian et al 2015Subramanian et al , 2016Srinivasan et al 2017). More importantly, because of the adverse effects of low temperatures on symbiosis, improving plant and microbiome performance and tolerance to cold stress, which depends on plant-symbiont, symbiont-symbiont interactions, and symbiont activity threshold under cold climatic conditions, requires more investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the antimicrobial potential of astaxanthin has direct health implications as this molecule was capable of reducing the bacterial load and gastric inflammation in mice infected with Helicobacter pylori [85,86]. In a different study, the antimicrobial capacity of astaxanthin was validated against different bacteria, including Escherichia coli, Proteus mirabilis, Aliivibrio fischeri, Enterobacter aerogenes, and L. monocytogenes, suggesting the potential of astaxanthin not only to produce safer foods but also to extend shelf-life [87]. Different antimicrobial polymers based on natural astaxanthin have been developed, with antimicrobial activities demonstrated in vitro with different pathogens minimizing bacterial growth and the formation of biofilms [88].…”
Section: Health Benefit Conditions Studied Comments Referencementioning
confidence: 99%
“…Spoilage of food incurs huge economic losses to producers (farmers), retailers, and consumers (Snyder, & Worobo, ). Storage temperature (Mageswari, Subramanian, Srinivasan, Karthikeyan, & Gothandam, ; Ndraha, Hsiao, Vlajic, Yang, & Lin, ; Odeyemi, Burke, Bolch, & Stanley, ), pH, water availability or moisture, improper storage (Bradford et al., ), indigenous microflora such as bacteria and fungi (Ioannidis et al., ), processing operations (Wang, He, & Yang, ), transportation (Hammond et al., ), and food handlers all influence the rate of spoilage. Aside from the problems of food insecurity and economic loss (Illikoud et al., ), spoiled food also contributes to food waste, which is another global environmental problem.…”
Section: Introductionmentioning
confidence: 99%